Artemisia herba alba & Artemisia monosperma: The Discovery of the first potential Egyptian plant sources for the Pharmaceutical Commercial Production of Artemisinin and Some of Its Related Analogues - El Motaz Bellah El Maggar (Journal of Applied Pharmaceutical Science)
Artemisinin has received considerable attention in the last few decades as the current drug of choice for treatment of malaria and a number of other diseases. Because of the development of resistance against other malarial drugs, the demand for artemisinin has rapidly increased during the past decade. However, the supply of artemisinin is troublesome as neither total nor semi-synthesis is economically feasible and the only plant species known to produce artemisinin, Artemisia annua L., contains only low amounts of this compound ranging from (0.01-0.6%) of dry weight. The wish to improve the overall supply of artemisinin at a reduced market price has encouraged interest to hit upon novel plant sources for artemisinin production as alternative to A. annua. In our current study a fingerprint profile method was developed for the detection and quantification of artemisinin and its related analogues in the methanolic extract of Artemisia monosperma and Artemisia herba alba using a high-performance liquid chromatography (HPLC) with diode-array detector (DAD) and ion trap mass spectrometry. Artemisinin, dihydroartemisinin (α and β isomers), artemisitene, dihydroartemisinic aldehyde, dihydroartemisinic acid, dihydroartemisinic alcohol were detected and quantified in the methanolic extract of Artemisia monosperma using LC-MS peak at concentrations of 3.6, 1.9, 0.27, 0.06, 0.08 and 1.95 % of dry plant weight respectively in addition to the detection of arteannuin B and artemisinic acid at a trace levels. While artemisinin, artemisitene, dihydroartemisinic acid, and artemisinic acid were detected and quantified in the methanolic extract of Artemisia herba alba at concentrations of 4.9, 0.35, 0.08 and 0.04 % of dry plant weight respectively. The high unexpected concentration of artemisinin and some of its related analogues detected in this study reported Artemisia herba alba and Artemisia monosperma for the first time as a novel potential plant sources for artemisinin and some of its related analogues that may be helpful for its commercial pharmaceutical production and could lead to the improvement of the overall supply of artemisinin at a reduced market price offering an acceptable price for most patients, especially that these Artemisia species are abundant in distribution in Egyptian desert.
Keywords: Artemisinin, Artemisinin Intermediate precursors involved in its biosynthesis pathway, Artemisia monosperma, Artemisia herba alba, High performance liquid chromatography-Mass spectrometry.